Bulky bracelet jewelry: Malaysian batik / Ahmad Faris Nor Anuwar - Nor Anuwar, Ahmad Faris (2022)
Bulky bracelet is a type of bracelet that have bigger size than a standard bracelet. Also be called as wide bracelet this jewelry product inspired by Malaysian batik to enhanced the arrangement of batik motif.